THE INFLUENCE OF JOB SATISFACTION AND MOTIVATION ON EMPLOYEES PERFORMANCE AT PT CHAKRA NAGA FURNITURE JEPARA - Rima Dian Safitri; Agus Suratno; EndangSulistiyani Sulistiyani (JOBS (Jurnal Of Business Studies), 2018)
This research aimed to analyze the influence of job satisfaction and motivation on employees performance at PT Chakra Naga Furniture Jepara. The method used for data collections was questionnaire using semantic differential scale. Using cencus sampling method, the sample of this research was all the employee of PT Chakra Naga Furniture Jepara a total 50 persons. The technique of analysis used in this research was multiple linear regression analysis. The analytical method used in this research were validity test and reliability test, classic assumption test, multiple linear regression, t-test, F-test and coefficient determination. The result of multiple linear regression could be shown by the regression equation Y=14,09 + 0,292X1 + 0,236X2. The results of this research indicate that partial and simultaneous, variable job satisfaction and motivation had positive influence and significant impact on employees performance. Coefficient of determination in this research was 0.718, which meant that 71.8% of employees performance could be influenced by job satisfaction and motivation, while the rest of 28.2% was explained by the other variables which were not observed.